Formation of NaH Molecules in the Lowest Rovibrational Level of the Ground Electronic State via Short-Range Photoassociation (Communications in Computational Physics, 2018)
The formation of NaH molecules in the lowest rovibrational level of theground electronic state is investigated using a pump-dump photoassociation (PA)scheme. In short-range region, two colliding atoms Na and H are efficiently associatedinto the NaH molecule in the rovibrational |0,0$〉$ state of the ground electronicstate via the intermediately rovibrational |10,1$〉$ state of the excited electronic state. Thechanges of populations with the electric field amplitudes, frequency detunings, dumppulse duration and delay time between two laser pulses are calculated and discussed.The PA probability reaches 0.623 with a high state-selectivity.